2014
DOI: 10.1152/ajpgi.00330.2013
|View full text |Cite
|
Sign up to set email alerts
|

Large intestine permeability is increased in patients with compensated liver cirrhosis

Abstract: Intestinal barrier dysfunction, facilitating translocation of bacteria and bacterial products, plays an important role in the pathophysiology of liver cirrhosis and its complications. Increased intestinal permeability has been found in patients with liver cirrhosis, but data on small and large intestine permeability and tight junctions (TJs) in patients with compensated cirrhosis are scarce. We aimed to investigate both small and large intestine permeability in patients with stable compensated cirrhosis compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
0
36
0
1
Order By: Relevance
“…The functional integrity of the epithelial barrier is maintained by intercellular tight junctions (TJs), which include the transmembrane protein occludin, claudins and the cytoplasmic protein zonula occludens 1 (ZO-1) (6). Intercellular TJ protein destruction is associated with a number of diseases, including cirrhosis (7). Therefore, restoring the integrity of the intestinal barrier is an important step in preventing intestinal endotoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…The functional integrity of the epithelial barrier is maintained by intercellular tight junctions (TJs), which include the transmembrane protein occludin, claudins and the cytoplasmic protein zonula occludens 1 (ZO-1) (6). Intercellular TJ protein destruction is associated with a number of diseases, including cirrhosis (7). Therefore, restoring the integrity of the intestinal barrier is an important step in preventing intestinal endotoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…Sandek et al [15] reported morphological and functional alterations of the gut in CHF patients, with an increased permeability index in both the small and large intestine. Pijls et al [35] reported an increased colonic permeability in patients with compensated liver cirrhosis. In patients with burn injuries, in patients undergoing cardiopulmonary bypass surgery and in critically ill patients who developed multi-organ failure, intestinal permeability was shown to be increased [36-40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using sugar as a differential marker in absorption tests, combining an oligosaccharide and a monosaccharide, such as in lactulose/mannitol (L/M) and saccharose/mannitol, revealed increased intestinal permeability in patients with liver cirrhosis 6,15,5759,8596…”
Section: Analytic Methods To Determine Intestinal Permeabilitymentioning
confidence: 99%
“…In patients with liver cirrhosis, alterations in intestinal permeability correlate with the degree of liver injury whereby Child–Pugh C patients and those with ascites or a positive history of SBP have increased intestinal permeability to the passage of molecules58 although patients with compensated cirrhosis have been shown to have increased colonic permeability but not gastroduodenal or intestinal 59. However, other authors have been unable to reproduce these results 60…”
Section: Intestinal Permeability In the Patient With Liver Cirrhosismentioning
confidence: 99%